2020
DOI: 10.3168/jds.2019-17767
|View full text |Cite
|
Sign up to set email alerts
|

Gene mapping and genomic prediction of bull fertility using sex chromosome markers

Abstract: Service sire has been recognized as an important factor affecting dairy herd fertility. Our group has reported promising results on gene mapping and genomic prediction of dairy bull fertility using autosomal SNP markers. Little is known, however, about the genetic contribution of sex chromosomes, which are enriched in genes related to sexual development and reproduction. As such, the main goal of this study was to investigate the effect of SNP markers on X and Y chromosomes (BTAX and BTAY, respectively) on sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…The contribution of the X-chromosome to phenotypic variation might be important for fertility or reproduction traits, e.g. [10][11][12]. Examples include variants that affect litter size in sheep, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of the X-chromosome to phenotypic variation might be important for fertility or reproduction traits, e.g. [10][11][12]. Examples include variants that affect litter size in sheep, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include variants that affect litter size in sheep, e.g. [13], infertility in cattle [14], or bull fertility [11]. More generally, quantitative trait loci (QTL) on the X-chromosome have been reported in previous studies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, bull fertility has been generally overlooked. Recent studies have reported promising results related to the feasibility of predicting dairy bull fertility using genomic data (Abdollahi-Arpanahi et al, 2017;Nani et al, 2019;Rezende et al, 2019;Pacheco et al, 2020). It should be noted that national dairy bull fertility evaluations are implemented in a few countries, including sire conception rate (SCR) in the United States and semen fertility value (SFV) in Australia (Carrick et al, 2000;.…”
Section: Introductionmentioning
confidence: 99%
“…This might be a particularity of the trait and/or population, or which may also be related to the presence of variance heterogeneity for the two traits (SC and P16). Pacheco et al (2019), evaluating the effect of sex chromosomes on reproductive traits in males and females, found an increase of 7.5% in the prediction ability of a model that considered the X chromosome together with the autosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Complementarily, the autosomes harbor genes with diverse functions and extremely heterogeneous expression patterns, while the sex chromosomes are rich in genes related to development and sexual reproduction (Liu, 2019). Within this context, some studies reported interesting results regarding the roles of the X chromosome in reproductive efficiency, including testicular development and spermatogenesis, female conception rate, and sexual differentiation, among others (Lynch and Walsh, 2007;Chang et al, 2013;Fortes et al, 2013;Lyons et al, 2014;De Camargo et al, 2015;Taylor et al, 2018;Pacheco et al, 2019). The inclusion of the effect of X chromosome markers also provided positive results by increasing the accuracy of genomic breeding value predictions (Su et al, 2014).…”
Section: Introductionmentioning
confidence: 99%